Meek and mild [large type] - Newport, Olivia (Newport, Olivia. Amish turns of time, 2015)
As the rift between Old Order Amish and the Marylanders widens, Clara and Andrew must examine their own hearts and consciences to seek God's will. The leadership in an Old Order Amish community requires shunning those whose only offense is embracing the new practice of Sunday school among the Mennonites. Yet teaching Bible stories to children is one of Clara's great joys. And now Andrew owns a car, flagrantly defying the bishop's authority. When Moses Beachy becomes bishop, they take bold steps toward change.